Recruitment strategies to promote uptake of cervical cancer screening in the West Region of Cameroon - Marie-Anne Pham; Khadidja Benkortbi; Bruno Kenfack; Eveline Tincho Foguem; Jessica Sormani; Ania Wisniak; Sophie Lemoupa Makajio; Engelbert Manga; Pierre Vassilakos; Patrick Petignat (BMC, 2022)
Abstract Objectives The World Health Organization's (WHO) global strategy for cervical cancer elimination has set the target of 70% of women screened in all countries by 2030. Community sensitization through media is often used, but community health workers' (CHW) involvement may contribute to improving screening coverage. We aimed to assess effectiveness and costs of two cervical cancer screening recruitment strategies conducted in a low-resource setting. Methods The study was conducted in the West Region of Cameroon, in the Health District of Dschang, a community of 300,000 inhabitants. From September 2018 to February 2020, we recruited and screened women for cervical cancer in a single-visit prevention campaign at Dschang District Hospital. During the first 9 months, recruitment was only based on Community Information Channels (CIC) (e.g.. street banners). From the tenth month, participation of CHW was added in the community after training for cervical cancer prevention counselling. Population recruitment was compared between the two strategies by assessing the number of recruited women and direct costs (CHW costs included recruitment, teaching, certification, identification badge, flyers, transport, and incentives). The intervention's cost-effectiveness was expressed using an incremental cost-effectiveness ratio (ICER). Results and discussion During the period under study, 1940 women were recruited, HPV positive rate was 18.6% (n = 361) and 39 cases of cervical intraepithelial neoplasia grade 2 or worse (CIN2+) were diagnosed. Among included participants, 69.9% (n = 1356) of women were recruited through CIC as compared to 30.1% (n = 584) by CHW. The cost per screened woman and CIN2+ diagnosed was higher in the CHW group. The ICER was 6.45 USD or 16.612021Int'l$ per screened woman recruited by CHW. Recruitment in rural areas increased from 12.1 to 61.4% of all women included between CIC-led and CHW-led interventions. These outcomes highlight the importance of training, preparing, and deploying CHW to screen hard-to-reach women, considering that up to 45% of Cameroon's population lives in rural areas. Conclusion CHW offer an important complement to CIC for expanding coverage in a sub-Saharan African region such as the West Region of Cameroon. CHW play a central role in building awareness and motivation for cervical cancer screening in rural settings.